High performance workforce: the influence of emotional intelligence and soft skills / Noorlaila Hj Yunus, Che Norlia Hassan, Noormala Amir Ishak - Hj Yunus, Noorlaila; Hassan, Che Norlia; Amir Ishak, Noormala (2011)
The primary cause of leadership failure in business organization today is poor interpersonal skills. Especially technicians promoted into leadership positions without much thought as to their readiness or suitability for leading people. These managers fail due to underdeveloped soft skills and lack of emotional intelligence. Emotional Intelligence is about knowing how to manage inter-intra personal relationships successfully. In order to get on in the work place you need to know your own strengths and weaknesses, your own true beliefs and then you need to know those of other people in order to get on with them and motivate them to produce the best work they possibly can. The 'soft' leadership principles are the major factor in what makes a high-performance team or organization. A manager needs to know how to perceive their staff and they need to be able to trust you.